Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've been posed a question in which I'm to differentiate with respect to $x$ a function of the form $(x+a)^k$. I've successfully completed (matches the book's answer) the question by using the chain rule, however I cannot achieve the same result using the definition of the derivative.

I would like a worked example of differentiation from first principles of a function of the form $(x+a)^k$.

share|cite|improve this question
Differentiation with respect to $x$? – user17794 Jul 7 '12 at 0:29
Yes. Question updated to reflect your feedback. – kobrien Jul 7 '12 at 0:30
Is there any particular reason why you want it done from first principles? Things like the chain rule were proved precisely so you don't have to do everything from first principles. – Potato Jul 7 '12 at 0:32
I'm aware the chain rule exists for this purpose, but it bothers me that I can't get it by first principles when it's a rather simple function. I'd like to see where I'm going wrong. It's for academic rather than practical benefit. – kobrien Jul 7 '12 at 0:35
up vote 4 down vote accepted

For concreteness, let's first take $k=3$.

We use the factorization $x^3-y^3=(x-y)(x^2+xy+y^2)$.

Here we have $(x+a+h)^3-(x+a)^3=h((x+a+h)^2+(x+a+h)(x+a)+(x+a)^2)$.

The difference quotient is then


As $h$ goes to zero, this becomes $3(x+a)^2$, as desired.

How does this generalize? We have similar factorizations for all $k$:

$$x^k-y^k=(x-y)(x^k+x^{k-1}y+\cdots xy^{k-1}+ y^k)$$

where there are $k$ terms in the second parenthesis. This factorization is easy to check, because the terms all telescope and cancel.

So what I did for $k=3$ can be repeated for general $k$, and when $h$ goes to zero you get $k$ terms of $(x+a)^{k-1}$ added together, which is exactly the same derivative you get using the chain rule.

share|cite|improve this answer
Excellent. Using this gave me the correct result. Thanks. – kobrien Jul 7 '12 at 1:00

$$ \frac{d}{dx} (x+a)^k = \lim_{h\to 0} \frac{1}{h}\left((x+h+a)^k - (x+a)^k\right) ~~. $$ The fundamental idea is, use the binomial theorem. $$ (x+h+a)^k = \sum_{j=0}^k {k \choose j} (x+a)^{k-j} h^j ~~, $$ so we notice that in the difference in the above limit, subtracting $(x+a)^k$ removes the $0^\text{th}$ term of the summation. Hence, $$ \lim_{h\to 0} \frac{1}{h}\left((x+h+a)^k - (x+a)^k\right) = \lim_{h\to 0} \frac{1}{h}\sum_{j=1}^k {k \choose j} (x+a)^{k-j} h^j $$ $$ = \lim_{h\to 0}\sum_{j=1}^k {k \choose j} (x+a)^{k-j} h^{j-1} = \lim_{h\to 0} \sum_{j=0}^{k-1} {k \choose j+1} (x+a)^{k-j-1} h^j ~~. $$ The summation expression can be thought of as a polynomial in $h$, so the only term which survives taking the limit will be when $j=0$. Hence, $$ \lim_{h\to 0} \sum_{j=0}^{k-1} {k \choose j+1} (x+a)^{k-j-1} h^j = {k \choose 1} (x+a)^{k-1} = k(x+a)^{k-1} ~~. $$ This is the simplest clean way I know of to solve this by the definition of derivative.

share|cite|improve this answer

We want to show that for any positive integer $n$, $$\lim_{h\to 0}\frac{(x+a+h)^n -(x+a)^n}{h}=n(x+a)^{n-1}.$$ To save typing, write $w$ instead of $x+a$. So we want to show that $$\lim_{h\to0}\frac{(w+h)^n-w^n}{h}=nw^{n-1}.$$ We prove the result by induction on $n$. The base step $n=1$ is easy. We prove the induction step, that if the result holds for $n=k$, it holds for $n=k+1$.

Note that $(w+h)^{k+1}=(w+h)^k (w+h)=w(w+h)^k +h(w+h)^k$. It follows that $$(w+h)^{k+1}-w^{k+1}=w((w+h)^k -w^k) +h(w+h)^k.$$ Divide by $h$. We get $$\frac{(w+h)^{k+1}-w^{k+1}}{h}=w\frac{(w+h)^k -w^k}{h} +(w+h)^k.\tag{$1$}$$ By the induction hypothesis, $$\lim_{h\to 0}w\frac{(w+h)^k -w^k}{h}=w(kw^{k-1})=kw^k.$$ And it is clear that $$\lim_{h\to 0}(w+h)^k=w^k.$$ So the right-hand side of $(1)$ has limit $(k+1)w^k$ has $h\to 0$. This completes the induction step.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.